International collaboration on prevention of shaken baby syndrome – an ongoing project/intervention. (November 2013) - Foley, Sue; Kovács, Zsuzsanna; Rose, Jenny; Lamb, Robyn; Tolliday, Fran; Simons-Coghill, Martine; Stephens, Amanda; Scheiber, Dóra; Toma, Andrea; Asbóth, Katalin; Kassai, Tamás; Agathonos, Helen; et al.
Abstract : Caring for young infants can be stressful. Non-accidental brain or head injury (shaken baby syndrome) is a result of parental stress, and a lack of knowledge of how to respond to a crying infant and the dangers of shaking a child. This article demonstrates the value of international collaboration in projects to prevent child maltreatment. It includes reports of prevention of shaken baby syndrome programmes in Australia, Hungary, Greece, Brazil and Turkey.